2023
DOI: 10.3390/ijms241411703
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Gut Microbiome Signatures Correlate with Immunogenicity of SARS-CoV-2 mRNA Vaccines

Abstract: The powerful immune responses elicited by the mRNA vaccines targeting the SARS-CoV-2 Spike protein contribute to their high efficacy. Yet, their efficacy can vary greatly between individuals. For vaccines not based on mRNA, cumulative evidence suggests that differences in the composition of the gut microbiome, which impact vaccine immunogenicity, are some of the factors that contribute to variations in efficacy. However, it is unclear if the microbiome impacts the novel mode of immunogenicity of the SARS-CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The Desulfobacterota can synthesize immunostimulatory endotoxin, its play a role in regulating SARS-CoV-2 mRNA vaccines immunogenicity. 36 In this study, the abundance of Desulfobacterota in the sepsis group was increased compared to the control group. This suggested that the Desulfobacterota abundance anomalies may be associated with the occurrence of sepsis.…”
Section: Discussionmentioning
confidence: 56%
“…The Desulfobacterota can synthesize immunostimulatory endotoxin, its play a role in regulating SARS-CoV-2 mRNA vaccines immunogenicity. 36 In this study, the abundance of Desulfobacterota in the sepsis group was increased compared to the control group. This suggested that the Desulfobacterota abundance anomalies may be associated with the occurrence of sepsis.…”
Section: Discussionmentioning
confidence: 56%
“…The gut microbiota influences the immunogenicity of the COVID-19 mRNA vaccines. A prospective cohort study found a positive correlation between pre-vaccination microbial diversity and composition (e.g., the phylum Desulfobacterota and genus Bilophila , synthesizing immunostimulatory endotoxin) and the final levels of anti-spike IgG [ 117 ]. Moreover, the antibiotic-induced depletion of the gut microbiome in mice was observed to reduce the immunogenicity of the Pfizer (BNT162b2) vaccine [ 117 ].…”
Section: Gut Microbiota Gender and Vaccinesmentioning
confidence: 99%
“…These results confirm that the gut microbiota composition influences the immunogenicity of SARS‐CoV‐2 mRNA vaccines. 179 The role of the gut microbiome in modulating the durability of immunity against COVID‐19 vaccines remains unclear. Gut microbiota sequencing and blood analysis at baseline, 1 month, and 6 months after vaccination revealed that multiple inflammatory factors, chemokines, and antibodies were associated with gut microbiota and metabolites, and that the abundance of some microbiota was associated with higher antibody levels at 6 months, suggesting that microbiota adjuvants may prolong the durability of the immune response to the SARS‐CoV‐2 vaccine.…”
Section: Microbiota‐based Implications For Therapeutic Interventionsmentioning
confidence: 99%